Gold Nanoclusters Potentially Facilitate Dentin Regeneration by Functioning Immunomodulation - Yang, Lan; Xiao, Lan; Liu, Tianqing; Gao, Wendong; Xiao, Yin (Frontiers in Materials, 2022)
The regeneration of dental pulp due to irreversible pulpitis remains as a challenge for regenerative dentistry. Pulpitis results in dentin destruction and exposure of dental pulp tissue to the infectious oral environment, thereby triggering continuous pulp inflammation which impedes the self-regenerative capacity of pulp. Thereby, the regeneration of dentin bridge to block pulp tissue from oral environment is an indispensable step for dental pulp regeneration. Although strategies, such as stem cell transplantation with scaffolds, have been applied to induce dentin regeneration, the important role of immunoregulation in pulp inflammatory microenvironment has been ignored. Our previous study found that the nanomaterial dihydrolipoic acid-functionalized gold nanoclusters (DHLA-AuNCs) could efficiently regulate inflammation via M1 to M2 phenotype switch of microglia (residential macrophages in the central nervous system), suggesting DHLA-AuNCs may exhibit a similar effect on the dental pulp macrophage response. In the current study, we found that DHLA-AuNCs could inhibit M1 phenotype while promote M2 phenotype in macrophages in inflammatory condition in vitro. This regulation of the inflammatory environment in dental pulp enhanced the differentiation of human dental pulp stromal cells (hDPSCs) towards odontoblasts, leading a beneficial effect on dentin regeneration. Additionally, DHLA-AuNCs were found to have a direct role on the differentiation and mineralization of human dental pulp stromal cells. The current study therefore demonstrated that DHLA-AuNCs could facilitate dentin regeneration through both efficient immunomodulation and direct induction on stromal cell differentiation/mineralization, providing a potential therapeutic nanomaterial for dental pulp regeneration.